Source and formation of the upper halocline of the Arctic Ocean. Issue 1 (31st January 2013) - Anderson, Leif G.; Andersson, Per S.; Björk, Göran; Peter Jones, E.; Jutterström, Sara; Wåhlström, Iréne
Abstract: [1] The upper halocline of the Arctic Ocean has a distinct chemical signature with high nutrient concentrations as well as low oxygen and pH values. This signature is formed in the Chukchi and East Siberian seas, by a combination of mineralization of organic matter and release of decay products to the sea ice brine enriched bottom water. Salinity and total alkalinity data show that the fraction of sea ice brine in the nutrient‐enriched upper halocline water in the central Arctic Ocean is up to 4%. In the East Siberian Sea the bottom waters with exceptional high nutrient concentration and low pH have typically between 5 and 10% of sea ice brine as computed from salinity and oxygen‐18 values. On the continental slope, over bottom depths of 150–200 m, the brine contribution was 6% at the nutrient maximum depth (50–100 m). At the same location as well as over the deeper basin the silicate maximum was found over a wider salinity range than traditionally found in the Canada Basin, in agreement with earlier observations east of the Chukchi Plateau. A detailed evaluation of the chemical and the temperature‐salinity properties suggests at least two different areas for the formation of the nutrient‐rich halocline within the East Siberian Sea. This has not been observed before 2004 and it could be a sign of a changing marine climate in the East Siberian Sea, caused by more open water in the summer season followed by more sea ice formation and brine production in the fall/winter. Key Points: Two different regions for the formation of AO upper halocline Brine enriched bottom water produce AO upper halocline Change in summer sea ice coverage can be important